Analysis of the role of the Cronobacter sakazakii ProP homologues in osmotolerance - Feeney, Audrey; Johnston, Christopher D; Govender, Rodney; O’Mahony, Jim; Coffey, Aidan; Sleator, Roy D (Gut pathogens, 2014)
Bacteria respond to elevated osmolality by the accumulation of a range of low molecular weight molecules, known as compatible solutes (owing to their compatibility with the cells' normal physiology at high internal concentrations). The neonatal pathogen Cronobacter sakazakii is uniquely osmotolerant, surviving in powdered infant formula (PIF) which typically has a water activity (a w ) of 0.2 – inhospitable to most micro-organisms. Mortality rates of up to 80% in infected infants have been recorded making C. sakazakii a serious cause for concern. In silico analysis of the C. sakazakii BAA-894 genome revealed seven copies of the osmolyte uptake system ProP. Herein, we test the physiological role of each of these homologues following heterologous expression against an osmosensitive Escherichia coli host.